TEORES DE SÓLIDOS EM DEJETOS DE BUBALINOS CRIADOS A PASTO - SANTOS, Marrony Gonçalves Pires dos; BEZERRA,Thaís dos Santos; SILVA, Fabiana Teodózio da; VALFRÉ, Lucas Rocha; CORREA, Jonas de Sousa; SANTOS, Tânia Mara Baptista dos (ANAIS DO ENIC, 2022)
-